2009
DOI: 10.1159/000247599
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-2 Gene Polymorphism Is Associated with Intracerebral Hemorrhage

Abstract: Background: Both ischemic stroke and intracerebral hemorrhage are associated with altered expression and activation of matrix metalloproteinases (MMPs). Particularly relevant are MMP-2 and MMP-9. This proteolytic effect is dampened by tissue inhibitors of metalloproteinases (TIMPs). TIMP-2 is an important endogenous inhibitor of MMP-2. Alterations in the TIMP-2 gene expression may contribute to the incidence of ischemic stroke and intracerebral hemorrhage. Methods: TIMP-2 gene SNP –261G/A was genotyped from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…TIMPs are the most important endogenous inhibitors of MMPs, in particular TIMP-1 and TIMP-2. Therefore, SNPs that lead to structural defects or modify the transcription rate of TIMP-2 could affect BBB breakdown and thereby influence the magnitude and/or incidence of ischemic stroke and intracranial hemorrhage [ 31 ]. SNPs can also interfere with the balance of MMPs and TIMP-2 in the absence of acute BBB disruption, thereby influencing the development and severity of atherosclerosis, white matter lesions, and small-vessel disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIMPs are the most important endogenous inhibitors of MMPs, in particular TIMP-1 and TIMP-2. Therefore, SNPs that lead to structural defects or modify the transcription rate of TIMP-2 could affect BBB breakdown and thereby influence the magnitude and/or incidence of ischemic stroke and intracranial hemorrhage [ 31 ]. SNPs can also interfere with the balance of MMPs and TIMP-2 in the absence of acute BBB disruption, thereby influencing the development and severity of atherosclerosis, white matter lesions, and small-vessel disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,7 In line with the original study design, subjects were recruited in two distinct cohorts. The first cohort comprised unselected consecutive patients with acute stroke-like symptoms, with stroke confirmed on subsequent imaging (CT scan or MRI), who consulted the Neurological Department of the Universitätsmedizin Mannheim within 24 hours of symptom onset.…”
Section: Subjectsmentioning
confidence: 99%
“…In addition, pro-MMP-2 in vitro increased gelatinolytic activity in cerebral aneurysms [ 17 ]. One study has shown genetic variation of TIMP-2 promoter increased ICH risks, suggesting that the MMP-TIMP pathway may play a role in the susceptibility to ICH risks [ 18 ].…”
Section: Introductionmentioning
confidence: 99%